Effect of CeO2 on Microstructure and Properties of Wear and Corrosion Resistance Martensitic Stainless Steel‐Based Coating on Laser Cladding. Issue 1 (18th September 2022) - Zhao, Fang; Guo, Tieming; Zhang, Yiwen; Wei, Xiaohong; Zhang, Ruihua; Nan, Xueli; Dong, Kang; Hu, Derong
Abstract : The effects of CeO2 on the quantity, morphology, and distribution of carbides, the microhardness, friction and wear properties, and corrosion resistance of 0.3C–16Cr martensitic stainless steel‐based cladding layer are investigated. The results show that the addition of CeO2 inhibits the dendrite growth and improves the morphology, size, and distribution of carbides in the cladding layer. The hardness shows a peak with the increase in CeO2 content, the wear rate of the cladding layer with CeO2 decreases, and the wear resistance increases. In addition, CeO2 significantly improves the corrosion resistance of the cladding layer, causing the pitting potential to increase and the blunt current density to decrease. Compared with the original sample, the wear amount and dimensional blunt current density of the sample with 0.3% CeO2 content are reduced by 55.36% and 35.32%, respectively, and the pitting potential is increased by 2.71 times. The comprehensive performance of the cladding layer is the best. This is mainly because CeO2 can increase the latent heat of crystallization during the cooling process of the cladding layer, reduce the constitutional supercooling, inhibit the directional growth of dendrites, improve the uniformity of the microstructure and composition, and thereby improve the wear resistance and corrosion resistance. Abstract : The effect of CeO2 on the corrosion resistance of stainless steel‐based cladding layers is illustrated in an eye‐catching color image. When CeO2 is added, the pitting potential and the width of the passivation zone all increase, the dimensional blunt current density decrease, and the corrosion resistance of the cladding layer is significantly improved.